THE ADOPTION AND USE OF MOODLE LEARNING MANAGEMENT SYSTEM IN HIGHER INSTITUTIONS OF LEARNING: A SYSTEMATIC LITERATURE REVIEW - Ziraba, Abdallah; Akwene, Godwill Chenyuei; Nkea, Atabong nee Alemanjoh Mariana; Lwanga, Shiynsa Charles (American Journal of Online and Distance Learning, 2020)
Purpose: This study had as purpose to examine the factors influencing instructors and students use of the Moodle Platform in teaching online courses in the ICT University, then the theories used in the use and adoption of Moodle platform. Methodology: The article focuses on the systematic review of empirical studies in the use and adoption of Moodle Learning Management System (MLMS) in higher institutions. The authors examined 58 publications on the subject from 2010 to 2019, making critical analysis of theories adopted in the study, the research approach, adoption factors, barriers, constructs used and research context. Findings: Findings from the literature review shown that technological factors, social factors, human factors and reinforcement factors affect the adoption and use of moodle platform. Most publications on this subject are reported using the quantitative research approach. Only a few studies have gained the attention of qualitative approach. Among the technology acceptance models used in the studies, TAM has gained more attention than any other has. The systematic review of literature has brought to the understand that institutes of higher learning in developed as well as developing countries are making remarkable progress in the Moodle Learning Management System (MLMS) as distance-learning tool for knowledge disseminate and acquisition. This practice however, has received more attention in the developed than in the developing countries. The outbreak of CCOVID-19 led to the promotion of social distancing. Institutions of higher learning can only become sustainable in the present dispensation if they promote the use of distance learning tools such as MLSM.